2014
DOI: 10.5511/plantbiotechnology.14.1008a
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting anabasine biosynthesis in tobacco hairy roots expressing plant lysine decarboxylase gene by using <sup>15</sup>N-labeled lysine

Abstract: Anabasine is an alkaloid found in a small number of Nicotiana species. The components of the anabasine biosynthetic pathway have yet to be identified. Here, we report the reinvestigation of biosynthetic pathways of anabasine and related tobacco alkaloids in genetically engineered cells. Hairy roots of N. tabacum harboring a lysine/ornithine decarboxylase gene from Lupinus angustifolius (La-L/ODC) were fed with labeled [ε-Relative to the unfed control, feeding of labeled 15 N-L-lysine greatly enhanced anabasine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Feeding with AL, EL or NL resulted in 17 (RPLC mode) and 23 (HILIC mode) specific metabolite features being labeled in both AL‐ and EL‐treated DC29 plants (Tables ; Table S5). Previously, feeding AL or EL to the hairy roots of Nicotiana tabacum harboring La‐L/ODC resulted in a similar labeling ratio of anabasine, an Lys‐derived alkaloid (Bunsupa et al ., ), which confirmed that anabasine was derived from cadaverine. Our results also show similar 15 N incorporation levels for the majority of specific metabolite features labeled in AL‐ and EL‐treated DC29 plants, suggesting that these metabolites are derived from cadaverine.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Feeding with AL, EL or NL resulted in 17 (RPLC mode) and 23 (HILIC mode) specific metabolite features being labeled in both AL‐ and EL‐treated DC29 plants (Tables ; Table S5). Previously, feeding AL or EL to the hairy roots of Nicotiana tabacum harboring La‐L/ODC resulted in a similar labeling ratio of anabasine, an Lys‐derived alkaloid (Bunsupa et al ., ), which confirmed that anabasine was derived from cadaverine. Our results also show similar 15 N incorporation levels for the majority of specific metabolite features labeled in AL‐ and EL‐treated DC29 plants, suggesting that these metabolites are derived from cadaverine.…”
Section: Discussionsupporting
confidence: 67%
“…Next, in order to evaluate the incorporation of exogenously applied l ‐lysine into specific metabolite features, the percentage isotope enrichment factors (%EFs) were calculated using the following formula: %EF = [(intensity of M + 1)/(sum of intensities of M and M + 1)] × 100, where M and M + 1 represent the monoisotopic mass of an unlabeled metabolite and a labeled metabolite with a mass shift of 0.997 Da, respectively. The %EF values were further corrected by taking into account the natural abundance of 15 N isotopolog peaks, as described previously (Campbell, ; Bunsupa et al ., ). Around 92.8–95.4% of l ‐lysine was labeled in DC29 treated with either AL or EL, whereas l ‐lysine was not labeled in DC29 treated with NL (Figure c).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Anabasine is composed of two rings, a piperidine ring derived from Lys and a pyridine ring derived from nicotinic acid. The two rings in nicotine are a pyrrolidine ring derived from Orn and a pyridine ring (Bunsupa et al, 2014). A negative correlation between LcL/ODC transcript and nicotine was found, but the nicotine levels did not decrease significantly.…”
Section: Physiological Importance Of Ldc For Alkaloid Productionmentioning
confidence: 86%
“…The decarboxylation of lysine (25) described in Hypothesis I would be performed by a P. granatum lysine decarboxylase (LDC). The presence of a lysine decarboxylase in the synthesis of anabasine (8) in Nicotiana species has been studied by the incorporation of [ 15 N]-lysine into anabasine (8) [124]. The methylation of cadaverine (26) would be achieved with the help of a P. granatum cadaverine N-methyltransferase (CMT).…”
Section: Granatane Alkaloid Biosynthesismentioning
confidence: 99%